Respuesta :

Answer:

Step-by-step explanation:

y=mx+b

so inset the first point into the equation

-3 for x and 7 for y.

7=m(-3)+b

y=mx+b

1 for x and -1 for y

-1=m(1)+b

now put them together and solve for m and b.

-1=m+b

7=-3m+b

--------------------

-1-b=m

7=-3m+b

inset m into the equation

7=-3(-1-b)+b

7=3+3b+b

4=4b

b=1

--------------

insert b back in for -1=m+b

-1=m+1

m=-2

---------------------------------------

Now insert it back into y=mx+b

y=(-2)x+1

so this line contains those points that were given

Hope this helps :)

ACCESS MORE